Authenticity and luxury branding in a renewing Detroit landscape. Issue 2 (4th May 2019) - Gregory, Siobhan
ABSTRACT: Emerging and establishing brands in Detroit regularly capitalize on the narrative of the city's "comeback." Many of these brands promote artisanal craftsmanship, nostalgia for an industrial past, and the repurposing of discarded materials as "authentic, " while others recast Detroit's image as a place of subsistence and survival and as one of "grit" and "hustle." Thus, the emerging image of a gentrifying Detroit is somewhat reliant on narratives of poverty and abandonment. These narratives are evident in the marketing materials used to sell luxury goods, services, and experiences. This article examines examples of digital and print marketing materials for Detroit-based product design and real estate development entities that illustrate how copywriting, imagery, and graphic design are brought together to deliver these messages.